2015
DOI: 10.1002/14651858.cd011984
|View full text |Cite
|
Sign up to set email alerts
|

Urine tests for Down's syndrome screening

Abstract: Tests involving second trimester ß-core fragment and oestriol with maternal age are significantly more sensitive than the single marker second trimester ß-core fragment and maternal age, however, there were few studies. There is a paucity of evidence available to support the use of urine testing for Down's syndrome screening in clinical practice where alternatives are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 456 publications
0
2
0
2
Order By: Relevance
“…(), 59 Alldred, Deeks, Guo, Neilson and Alfirevic (), 60 Alldred et al. (), 61 Alldred et al. (), 62 Soares‐Weiser et al.…”
Section: Resultsunclassified
“…(), 59 Alldred, Deeks, Guo, Neilson and Alfirevic (), 60 Alldred et al. (), 61 Alldred et al. (), 62 Soares‐Weiser et al.…”
Section: Resultsunclassified
“…There is a paucity of evidence available to support the use of urine testing for Down's syndrome screening in clinical practice where alternatives are available. 13 Alldred SK et al reported that meta-analysis of the six most frequently evaluated test combinations showed that a test strategy involving maternal age and a combination of first trimester NT and PAPP-A, and second trimester total hcG, uE3, AFP and Inhibin A significantly outperformed other test combinations that involved only one serum marker or NT in the first trimester, detecting about nine out of every 10 Down's syndrome pregnancies at a 5% false positive rate. 14 Alldred SK et al reported that meta-analysis of 12 best performing or frequently evaluated test combinations showed double and triple tests (involving AFP, uE3, total hcG, free hcG) significantly outperform individual markers, detecting six to seven out of every 10 Down's syndrome pregnancies at a 5% false positive rate.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the levels found in urine will be in luenced by maternal blood levels and the different metabolic rates of the molecules will be re lected in our analysis. This has not been fully appreciated when urinary marker tests for Downs Syndrome screen have been evaluated previously [25]. The m/z bin centile distribution plots make no assumption as to the normality of distribution of the data; which for each group, and at each m/z, could be Gaussian but are frequently skewed.…”
Section: Gestational Age Correctionmentioning
confidence: 99%